Survival and lung function decline in patients with definite, probable and possible idiopathic pulmonary fibrosis treated with pirfenidone - Májek, Ondřej; Gregor, Jakub; Mogulkoć, Nesrin; Lewandowska, Katarzyna; Šterclová, Martina; Müller, Veronika; Hájková, Marta; Kramer, Mordechai R; Tekavec-Trkanjec, Jasna; Jovanović, Dragana; Studnicka, Michael; Stoeva, Natalia; et al. (PloS one, 2022)
BACKGROUND: There is no clear evidence whether pirfenidone has a benefit in patients with probable or possible UIP, i.e. when idiopathic pulmonary fibrosis (IPF) is diagnosed with a lower degree of diagnostic certainty. We report on outcomes of treatment with pirfenidone in IPF patients diagnosed with various degrees of certainty. METHODS AND FINDINGS: We followed patients in the multi-national European MultiPartner IPF Registry (EMPIRE) first seen between 2015 and 2018. Patients were assessed with HRCT, histopathology and received a multi-disciplinary team (MDT) IPF diagnosis. Endpoints of interest were overall survival (OS), progression-free survival (PFS) and lung function decline. RESULTS: A total of 1626 patients were analysed, treated with either pirfenidone (N = 808) or receiving no antifibrotic treatment (N = 818). When patients treated with pirfenidone were compared to patients not receiving antifibrotic treatment, OS (one-, two- and three-year probability of survival 0.871 vs 0.798; 0.728 vs 0.632; 0.579 vs 0.556, P = 0.002), and PFS (one-, two- and three-year probability of survival 0.597 vs 0.536; 0.309 vs 0.281; 0.158 vs 0.148, P = 0.043) was higher, and FVC decline smaller (-0.073 l/yr vs -0.169 l/yr, P = 0.017). The benefit of pirfenidone on OS and PFS was also seen in patients with probable or possible IPF. CONCLUSIONS: This EMPIRE analysis confirms the favourable outcomes observed for pirfenidone treatment in patients with definitive IPF and indicates benefits also for patients with probable or possible IPF.
Keywords: vitální kapacita; plíce; pravděpodobnost; antiflogistika nesteroidní; Anti-Inflammatory Agents, Non-Steroidal; lidé; retrospektivní studie; Idiopathic Pulmonary Fibrosis; Lung; pyridony; Probability; idiopatická plicní fibróza; Retrospective Studies; Treatment Outcome; Pyridones; výsledek terapie; Vital Capacity; Humans